Impact of humidity in triple cation perovskite solar cells: Surface analysis. (December 2022) - Hsu, Rui-Yun; Liang, Yuan-Jun; Hung, Yu-Jen; Lin, Yi-Cheng
Abstract: Perovskite (PVSK) is widely used in the absorber layer of solar cells due to its excellent conversion efficiency; however, these devices are highly susceptible to humidity. Furthermore, the mechanism underlying the moisture-induced performance degradation in triple cation PVSK has yet to be elucidated. In the current study, we used the anti-solvent method to prepare triple cation PVSK films in order to study the growth mechanism and influence of moisture on conversion performance. We determined that an appropriate quantity of moisture in PVSK films can improve grain growth of PVSK and increase the difference in potential energy between grain and grain boundary, thereby facilitating the transport and collection of carriers across grain boundaries. Excess moisture entering PVSK thin films leads to degradation of the PVSK absorber layer, resulting in the formation of PbI2, PbBr2, HI, FAI, and MABr, while leaving holes in the surface, which can compromise the stability of the crystals and efficiency of the solar cell. In the current study, the efficiency of PVSK thin film solar cells was 19.14% under an optimal humidity level 25%, which resulted in photoelectric characteristics and device efficiency on par with the results obtained under a pure nitrogen environment. Graphical abstract: Image 1 Highlights: The mechanism underlying the moisture-induced degradation of triple cation perovskite films was studied. An appropriate quantity of moisture in perovskite films can improve crystallinity and passivate grain boundaries. Device efficiency under optimum humidity conditions is 19.05%, which is comparable to pure nitrogen.